Network pharmacology analysis of bioactive compounds and potential targets of Basella alba for psoriasis treatment - Oktavriana, Triasari; Kariosentono, Harijono; Purwanto, Bambang; Widyaningsih, Vitri; Irawanto, Muhammad E (International Journal of Innovative Research and Scientific Studies, 2025)
Psoriasis is a chronic inflammatory skin disease characterized by a complex and multifaceted pathophysiology. Due to its persistent and recurrent nature, it poses significant global health challenges, including increased risks of medication resistance, adverse side effects, and systemic comorbidities. Consequently, there is ongoing research into the use of various medicinal plants for its treatment. This research aims to investigate the bioactive compounds of Basella alba and their potential in treating psoriasis. A network pharmacology analysis was conducted to elucidate the relationship between the bioactive compounds of Basella alba and psoriasis. The Lipinski Rules of Five were followed for screening Basella alba compounds in order to find secondary metabolite compounds that met the established criteria. Swiss Target Prediction was used to predict the target protein, while Gene Cards was used to identify psoriasis-related proteins. Venny was used to perform the intersection of these findings. A network pharmacology analysis was conducted using String-DB, and the results were subsequently enriched through the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. The selection results identified 22 Basella alba active compounds, 11 of which fulfilled Lipinski's Rule of Five. Gene Cards identified 632 psoriasis-related proteins. Predictions showed that Basella alba bioactive compounds interact with 1,179 proteins, with 241 overlapping. Basella alba treats psoriasis by targeting TP53, AKT1, TNF, EGFR, IL6, STAT3, IL1B, GAPDH, BCL2, and MYC. Bioactive compounds in Basella alba, including beta-carotene, acacetin, kaempferol, bioflavonoid (rutin), Basella saponin C, and stigmasterol glucoside, may have antipsoriatic effects through apoptotic pathways and inflammation. This research suggests that the bioactive compounds of Basella alba have the potential to be effective natural treatments for psoriasis.